1998
DOI: 10.1021/jo980238u
|View full text |Cite
|
Sign up to set email alerts
|

Pericyclic versus Pseudopericyclic 1,5-Electrocyclization of Iminodiazomethanes. An ab Initio and Density Functional Theory Study

Abstract: Density functional (B3LYP/6-311+G) and ab initio (MP2/6-311+G and MP4(SDTQ)/6-311+G//MP2/6-311+G) calculations on the ring closure reactions of (E)- and Z-iminodiazomethane ((E)-5, (Z)--5), vinyldiazomethane 7, and formyldiazomethane 9 to 1H-1,2,3-triazole 6, 3H-pyrazole 8, and 1,2,3-oxadiazole 10, respectively, are reported. (E)-5 cyclizes via a low barrier (ca. 10 kcal mol(-)(1)) pseudopericyclic nonrotatory transition state. Ring closure of (Z)-5 and 7 proceeds by a monorotatory movement of the imino or vin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 48 publications
1
49
0
1
Order By: Relevance
“…22 Computational investigations have provided evidence that psuedopericyclic transition states are typically planar with no rotation of the terminal π-bonds. For instructive reviews of the subject, the reader is directed to articles of Kappe et al, 23 Birney et al, 24 and references therein. Isomerization of 7a via 8a forms the more stable product 7a ′.…”
Section: Resultsmentioning
confidence: 99%
“…22 Computational investigations have provided evidence that psuedopericyclic transition states are typically planar with no rotation of the terminal π-bonds. For instructive reviews of the subject, the reader is directed to articles of Kappe et al, 23 Birney et al, 24 and references therein. Isomerization of 7a via 8a forms the more stable product 7a ′.…”
Section: Resultsmentioning
confidence: 99%
“…Por ex., o 4-carboxiamida-5-metilamino-1,2,3-triazol (50a) quando aquecido a 160 o C rearranja-se, produzindo 5-amino-4-carboxiamida-1-metil-1,2,3-triazol (50b) (Esquema 11) 41 . Recentemente, Fabian e Bakulev 42 utilizando cálculos teóricos confirmaram a proposta de que ocorre uma ciclização pseudopericíclica. Muitos outros trabalhos mostraram que este rearranjo também ocorre em triazóis contendo os substituintes diazometil 43 , amino [43][44][45] .…”
Section: Metodologia Via Ciclização [2n + 1n]unclassified
“…[5] Recently, we [6] and others [7] have demonstrated that transition metal azavinyl carbenes can be accessed directly from certain electron-deficient 1,2,3-triazoles, [8] likely due to the ring-chain tautomerism of the latter. [9] Among the reactive triazoles are 1-sulfonylated derivatives which can be synthesized in multigram amounts, isolated, and safely stored, [8e] or can be generated in situ from stable N H -triazoles, 1 , with triflic anhydride under mild conditions (Scheme 1). [6d] In the presence of Rh(II) catalysts, N -triflyl triazoles formed in this way are readily converted to azavinyl carbenes that readily react with a variety of olefins, 2 , yielding highly enantioenriched cyclopropane carboxaldehydes, 3 .…”
mentioning
confidence: 99%